The relationship between leg muscle strength and functional mobility in the elderly - I Gede Made Nugi Nugraha; I Made Niko Winaya; Anak Agung Gede Angga Puspa Negara; Ni Luh Nopi Andayani (Physical Therapy Journal of Indonesia, 2024)
Background: The elderly are individuals who experience a slow ageing process that can cause a decrease in physical function and condition. A noticeable decrease in function in the elderly is a decrease in muscle mass. This study aimed to determine the relationship between leg muscle strength and functional mobility ability in the elderly. This study aimed to determine the relationship between leg muscle strength and functional mobility in the elderly. Methods: The design of this study was observational analytic with a cross-sectional study direction. At the research site at Puskesmas II Tabanan, the number of research subjects was 63 older people aged 60-69 years. A 30-second chair stand test measures leg muscle strength, while a timed up-and-go test measures functional mobility ability. Results: The results of the association test using Spearman's Rho Test obtained a correlation coefficient value (r) -0.535 with a p-value=0.000 (p<0.05), which means there is a strong significant relationship that is negative in both variables. Conclusion: There was a strong negative significant relationship between leg muscle strength and functional mobility ability in the elderly at Puskesmas II Tabanan.